Optimal Spacing of Tubewells In Relation to Channel Losses and Lining for Multicropping System in Coastal Orissa - Paul, Jagadish Chandra; Mishra, Jayanarayan (Journal of Agricultural Engineering, 2008)
Taking into account the different fixed and operating cost components of water production, a mathematical model was developed for optimal spacing of shallow tubewells in relation to channel lining and conveyance losses for multicropped tubewell command area. Area allocated to various crops and their depths of irrigation were considered for this purpose. The model was solved for shallow tubewell conditions of Mahandi delta of coastal Orissa. Optimum spacing of 400 m was found when 80% of the channel length was considered lined. The cost of water production for the study area worked out to a minimum of Rs.298/- per 100 mÂ³ volume of water. For unlined channel an optimum spacing of 120 m was found for which the cost of water production resulted to be Rs.369/- per 100 mÂ³ volume of water.